Identifying Conceptual Mistakes on SMA Teaching Books in Materials of Imune System for Eleventh Graders - Pangestika, Aprilia; Widyaningrum, Trianik (International Journal of Active Learning, 2018)
Textbooks as compulsory reference books containing misconceptions may prevent students from learning. This study aims to determine the mistakes of the concepts contained in biology textbooks especially immune system material and to determine the percentage of mistake concept. This research belongs to the type of evaluation research and data collection techniques used is documentary study. The object of research in this study is immune system material in a textbook published by Erlangga, Yudhistira, and Grasindo. In order to facilitate this research, the books are each given a symbol A, B and C. Identification mistake concept in this study used the standard criteria of mistake according to the concept Dikmenli (2009) and Hersey (2004) which include: Oversimplifications, Overgeneralizations, Undergeneralizations, Obsolete Concept and Terms, and Misidentifications. Immune system materials in textbooks that are used as objects in this study are identified to contain mistakes of the concept categories namely Oversimplifications, Overgeneralizations, Undergeneralizations, and Misidentifications. The percentage of each category for book A is 23.5%; 5.9%; 5.9% and 5.9%; that of book B is 41.2%; 17.6%; 0% and 11.8%; while that of book C is 58,8%; 0%; 11.8% and 11.8% respectively. The results of this study indicate that the mistake of the concept on the books is very fatal. Therefore, the preparation of textbooks must meet the criteria of instructional materials according to BSNP covering four aspects, namely content, language, graphics and serving content (techniques, materials, and learning).